FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMANAN BARANG MILIK DAERAH DI KOTA PALEMBANG - Hidayat, Ahmad Maulana Arif; Rachmasari, Kartika; Aryani, Yuli Antina (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The Influence of Regional Property Management on Security of Regional Property in Palembang City This study aims to determine the effect of Regional Asset Administration on the Security of Regional Assets in Palembang City. This research method uses quantitative research using Primary data in the form of questionnaires obtained from each Regional Apparatus Organization in Palembang City. The population and sample of this study were 32 Regional Apparatus Organizations in Palembang City. The data analysis technique is multiple linear regression analysis with the help of SPSS software version 29. The results show that partially the bookkeeping variable does not have a positive and significant effect, while the inventory and reporting variables have a positive and significant effect. Simultaneously, the bookkeeping, inventory and reporting variables have a positive and significant effect of 25.8%